A Redox‐Switchable Germylene and its Ligating Properties in Selected Transition Metal Complexes. Issue 5 (23rd December 2016) - Walz, Florian; Moos, Eric; Garnier, Delphine; Köppe, Ralf; Anson, Christopher E.; Breher, Frank
Abstract: The synthesis, structure, and full characterization of a redox‐switchable germylene based on a [3]ferrocenophane ligand arrangement, [Fc(NMes)2 Ge] (4 ), is presented. The mesityl (Mes)‐substituted title compound is readily available from Fc(NHMes)2 (2 ) and Ge{N(SiMe3 )2 }2, or from the dilithiated, highly air‐ and moisture‐sensitive compound Fc(NLiMes)2 ⋅3 Et2 O (3 ) and GeCl2 . Cyclic voltammetry studies are provided for4, confirming the above‐mentioned view of a redox‐switchable germylene metalloligand. Although several 1:1 Rh I and Ir I complexes of4 (5 –7 ) are cleanly formed in solution, all attempts to isolate them in pure form failed due to stability problems. However, crystalline solids of [Mo(κ 1 Ge ‐4 )2 (CO)4 ] (8 ) and [W(κ 1 Ge ‐4 )2 (CO)4 ] (9 ) were isolated and fully characterized by common spectroscopic techniques (8 by X‐ray diffraction). DFT calculations were performed on a series of model compounds to elucidate a conceivable interplay between the metal atoms in neutral and cationic bimetallic complexes of the type [Rh(κ 1 E ‐qE )(CO)2 Cl] 0/+ (qE =[Fc(NPh)2 E] with E=C, Si, Ge). The bonding characteristics of the coordinated Fc‐based metalloligands (qE /qE + ) are strongly affected upon in silico oxidation of the calculated complexes. The calculated Tolman electronic parameter (TEP) significantly increases by approximately 20 cm −1 (E=C) to 25 cm −1 (E=Si, Ge) upon oxidation. The change in the ligand‐donating abilities upon oxidation can mainly be attributed to Coulombic effects, whereas an orbital‐based interaction appears to have only a minor influence. Abstract : The redox‐switchable germylene [Fc(NMes)2 Ge], based on a [3]ferrocenophane ligand arrangement, alongside some transition‐metal complexes are reported. The changes in the ligating properties upon oxidation were elucidated by DFT calculations on neutral and cationic bimetallic model complexes.